Women with fetal death: nurses' care limitations - Joice Moreira Schmalfuss; Regina Yoshie Matsue; Lucimare Ferraz
ABSTRACT Objective: To present the limitations of the nursing care for women with fetal death, reflecting on this challenge for care practices. Method: Reflective study with theoretical focus on national and international publications, along with the experience of the authors in the area of women's health and obstetrics. Results: There are limitations related to nursing care, which involve feelings of insecurity and powerlessness, inappropriate attitudes of these professionals in front of women, difficulties to manage emotional aspects, and structural problems of health services. Final Considerations: This study points out that there are challenges to qualify nursing care for women with fetal death, which included academic studies and continuing education in health services. Relational aspects should be valued and demand more sensitivity from nurses, with more empathic relationships in the care for women with fetal death.